Estudo de Ligas Fe-Nb-B Nanocristalinas Eutéticas Ultrafinas e Laser Cladding de Pós Atomizados - Caneda, Chaiane Messa (Universidade Federal de São Carlos, 2020)
Fe-Nb-B alloys have gained much attention in recent years because of the possibility to obtain different constituents in nanostructured composites, amorphous and ultrafine eutectics (scale of 100 nm to 1 μm) alloys depending on composition and cooling rate. These structures are originated by rapid solidification in non-equilibriun balance and have excellent mechanical (high hardness, high resistance to fracture and plasticity) and chemical properties. LASER processing is considered one of the routes that also allows the development of these structures, enabling new perspectives on technological applications of these alloys. This work presents aimed the development of ultrafine eutectic nanocrystalline Fe-Nb-B alloys seeking to evaluate the mechanical behavior on strength and ductility. From these selected compositions for the subsequent production of gas atomized powders were manufacturing the coatings of these alloys onto AISI 1020 mild steel substrate by LASER cladding using a pre-placed powder method. The compositions in which the coatings were produced, Fe76.5Nb8.5B15 and Fe74.25Nb8.25B17.5 (at. %), allowed to investigate the appropriate parameters ranges to obtain coatings with high microhardness and at the same time, with possible wear resistance. Both coatings were characterized using the techniques of X-ray Diffraction (DRX), Scanning (SEM) and Transmission Electron Microscopy (TEM) of a samples prepared by Focused Ion Beam (FIB) allowed the analysis of the formation of eutectic phases (as predicted).The wear resistance of coatings for Fe76.5Nb8.5B15 (at.%) alloy were evaluated through the pin-on-disk test with three-body abrasive indicated lower wear rates values compared to the steel substrate (1.9 x 10-5 to 3.9 x 10-5 mm³/Nm, respectively).
Study of Fe-Nb-B ultrafine Eutetic Alloys and Laser Cladding of Atomized Powders
Keywords: Ligas Fe-Nb-B; LASER cladding; Revestimentos eutéticos ultrafinos; Propriedades de desgaste; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA DE TRANSFORMACAO